Global skill partnerships: A proposal for technical training in a mobile world - Michael A. Clemens (IZA Journal of Labor Policy, 2015)
Skilled workers emigrate from developing countries in rising numbers, raising fears of a drain on the human and financial resources of the countries they leave. This paper critiques existing policy proposals to address the development effects of skilled migration. It then proposes a new kind of ex ante public-private agreement to link skill formation and skilled migration for the mutual benefit of origin countries, destination countries, and migrants: 'Global Skill Partnerships'. The paper describes how such an agreement might work in one profession (nursing) and one region (North Africa), and offers design lessons from related initiatives around the world.
Keywords: F22; J24; O15; 330; Brain drain; Development; Education; Finance; Health; Nurse; Eldercare; Mobility; Aging; Migration